Pengaruh Jumlah Simpanan dan Jumlah Pinjaman terhadap Sisa Hasil Usaha pada Koperasi Unit Desa Mambal, Kecamatan Abiansemal, Kabupaten Badung - PUTRI RAHMAWATI DEWI S; KETUT BUDI SUSRUSA; I KETUT RANTAU (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2019)
The Effect of the Amount of Deposits and Lending Credit on Profits of VillageUnit Cooperatives of Mambal, Sub-District of Abiansemal, Badung Regency Cooperatives are legal entities established by individuals or cooperative legal entities,with the separation of the wealth of their members as capital to run a business to meetcommon needs. One of the forms of cooperative development is the village unitcooperative. Factors that influence the existence of cooperatives in the midst of theglobal economy are the amount of net income they have. The Mambal Village UnitCooperative has carried out several businesses in order to obtain maximum profits.Efforts are made, namely by carrying out activities to raise funds, both from membersand from the public in the form of deposits and credits. This study aims to determine theeffect of the total of deposits and amount of credits on the profits. This research wasconducted at the Mambal Village Cooperative Unit, Abiansemal Sub-District, BadungRegency. This study uses multiple linear regression analysis. The results of the studyshowed that simultaneously the amount of deposits and the amount of credits had apositive and significant effect on the profits of the Mambal Village Unit Cooperative.Partially the amount of deposits has a positive and significant effect on the profits at theMambal Village Cooperative Unit, while the amount of credits has a positive and notsignificant effect on the profits of the Mambal Village Unit Cooperative.